SEMIOTIKA DALAM LIRIK LAGU “INTERAKSI” KARYA TULUS - Alwafa Shandy Hermawan; Rini Damayanti (Cakrawala Indonesia, 2022)
This article examines the semiotic meaning of the lyrics of the song "Interaksi" by Tulus through Roland Barthes' semiotic analysis. The meaning expressed is the meaning of denotation, connotation, and myth. The research method used is an interpretive qualitative method or an inductive way of thinking, namely a way of thinking from the specific to the general. The data collection technique used is document study, namely tracing and obtaining from various sources where the data is needed. The results of the semiotic study of the lyrics of the song "Interaksi" are as follows. The denotative meaning of the lyrics of the song "Interaksi" there are several words, phrases, or sentences that need to be known the denotative meaning, for example the word "Interaction". The word interaction means influencing, attracting, asking and giving. The connotation meaning of the lyrics of the song "Interaksi" can be interpreted as a romantic relationship, which positions Tulus as someone who hopes to fall in love with the person he likes. The connotative meaning obtained is related to the mythical meaning in the lyrics of this song. From the overall analysis of the song lyrics, the meaning of the myth is obtained, Tulus would like to convey that expectations are something that is needed by everyone who is in a romantic relationship. In this case, the expectations the songwriters experience so they can know if they still like each other or need each other. The existence of expectation or hope is to be able to find an answer in this case is a love relationship.